Dynamics of Women Fertility in Austria, Bulgaria and the Czech Republic from 1985 to 2008 - Kaloyanov, Todor (Research Papers, 2010)
As a synthetic estimator, the total fertility rate helps to establish the level of fertility of women at a particular moment and to follow the basic development of its dynamics. The information provided by this estimator is really important, but, just like any other total measurement, it cannot reveal the mechanism by which its value is formed.When the purpose is to establish the changes in the reproductive behaviour of women, the factors whose influencedetermines these changes and the differences in the behaviour of women from various generations, then other means of analysis are necessary. It is necessary to use additional methods which can reveal the mechanism of forming the particular level of fertility. One approach to solving such a task is to study the distributions of the age-related fertility rate.The current study analyses the dynamics of the distributions of the fertility of reproductive-age women in Austria, Bulgaria and the Czech Republic in the period between 1985 and 2008. In addition to the total fertility rate, the research uses the dynamics of the distribution of the fertility coefficients by age. To be more precise, it studies the changes in the values of the sequences consisting of the average age, the standard deviation and the asymmetry and excess coefficients.The comparative analysis that has been carried out made it possible to establish the common features in the nature of the changes that are taking place in the reproductive behaviour of  women in Austria, Bulgaria and the Czech Republic, as well as to reveal the differences in the speed and the scale of these changes over the last twenty years.This study made it possible to evaluate the effect of the process of transformation, which started in the 1990ies in Bulgaria and the Czech Republic, on the changes of women’s reproductive model.